Trumpism and the European Far Right: An Analysis of Trumpism’s Impact on the Post-2016 AfD, Lega Nord, and Fidesz - Fusiek, Dawid Aristotelis; Marconi, Cecilia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The paper aims at investigating the relationship between Trumpism and the European far-right parties. The combination of shared ideological cores with the confrontation of similar “enemies” has resulted in the creation of an unprecedented relationship, wherein Trump takes the role of “international godfather” and inspiration for the European far right. To examine this relation, the paper focuses on references to Donald Trump and his policies and statements from 2016 to 2020 in the discourse of Alternative für Deutschland (AfD), Hungarian Civilian Alliance (Fidesz), and Lega Nord (Lega). The examination of the discourse of the three parties about security, immigration, foreign policy, and corruption shows that these parties have utilised Trumpism in three manners. Firstly, they have employed Trumpism to normalise certain pre-existing far-right ideologies and practices within their national and European context. Secondly, they have emulated Trump’s discourse and policies to capitalise on his popularity and support their national endeavours. Thirdly, they have used Trump’s fight and ideas to justify national measures, beliefs, criticism, or political goals. This paper thus aims to establish the leitmotifs governing the use of Trumpism by European far right to set the framework for future more critical analyses and a better understanding of this unprecedented relationship.

Celem artykułu jest zbadanie relacji między Trumpizmem a skrajnie prawicowymi partiami politycznymi w Europie. Połączenie wspólnych rdzeni ideologicznych i konfrontacji z podobnymi „wrogami” doprowadziło do powstania niespotykanej dotąd relacji, w której Trump odgrywa rolę „międzynarodowego ojca chrzestnego” i inspiratora europejskiej skrajnej prawicy. W celu zbadania tej relacji praca skupia się na odniesieniach do aktywności Donalda Trumpa, jego polityki i wypowiedzi w latach 2016–2020 w dyskursie Alternative für Deutschland (AfD), Węgierskiej Partii Obywatelskiej (Fidesz) i Lega Nord (Lega). Analiza dyskursu trzech partii w zakresie bezpieczeństwa, imigracji, polityki zagranicznej i korupcji pokazuje, że partie te wykorzystały Trumpizm jako inspirację w trzech aspektach. Po pierwsze, użyły go do normalizacji wcześniej istniejących skrajnie prawicowych ideologii i praktyk w kontekście narodowym i europejskim. Po drugie, naśladowali dyskurs Trumpa i jego polityki do zwiększenia jego popularności i wsparcia własnych dążeń narodowościowych. Po trzecie, wykorzystali walkę i idee Trumpa do uzasadnienia narodowych metod, wierzeń, krytyk i celów politycznych. W związku z tym artykuł ma ustalić główne motywy do wykorzystania Trumpizmu przez europejską skrajną prawicę do ustanowienia podwalin dla przyszłych analiz krytycznych i lepszego zrozumienia tej niespotykanej relacji.
Trumpizm i Europejska skrajna prawica: Analiza wpływu Trumpizmu na AfD, Lega Nord i Fidesz po 2016 roku
Keywords: Trumpism; European far-right; populism; AfD; Fidesz; La Lega Nord; Trumpizm; europejska skrajna prawica; populizm; AfD; Fidesz; La Lega Nord